ANALISIS PENGGANTIAN KOMPONEN MESIN TUBE SPLICING DAN MESIN TUBE CURING DENGAN DISTRIBUSI WEIBULL DAN PERHITUNGAN EFISIENSI BIAYA DI PT GAJAH TUNGGAL TBK - Budi Ariyanto (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstract: Industrial problems about spare parts/production equipment replacement is one of the very important issue, because this issue relates to the cost that must be issued , both as a consequence of the replacement appliance, repair or the most fatal is the lost production due to the damage. PT Gajah tungal Tbk is a large company with a very much number and type of machines or production equipment. With the number reached 2,569 machines, of course, engine components / spare parts for these machines are very many and need to be replaced periodically to maintain reliability of these machines . Replacement engine components often occurs when the engine failure has occurred. The number of machines in the PT Gajah Tunggal Tbk requires an effective and efficient component maintenance system. The purpose of this study was to determine the reliability of the replacement of machine components O - Ring Seal on Tube Splicing machines and motor on Tube Curing machine with weibull distribution.This study using software weibull 9 ++for the determination of a suitable distribution and determine the optimal time replacement components of the O-ring Seal on Tube Splicing machine and Motor on Tube Curing machine. Then the results are applied to compare the cost of maintenance of the components in the event of replacement with the replacement schedule. The result shows that weibull distribution can help determine the reliability of the preventive maintenance engine components which impact to increases the efficiency of maintenance cost.Keywords: Preventive Maintenance, Reliability, Weibull Distribution.